Wnt3a upregulates brain-derived insulin by increasing NeuroD1 via Wnt/β-catenin signaling in the hypothalamus. Issue 1 (December 2016) - Lee, Jaemeun; Kim, Kyungchan; Yu, Seong-Woon; Kim, Eun-Kyoung
Abstract Background Insulin plays diverse roles in the brain. Although insulin produced by pancreatic β-cells that crosses the blood–brain barrier is a major source of brain insulin, recent studies suggest that insulin is also produced locally within the brain. However, the mechanisms underlying the production of brain-derived insulin (BDI) are not yet known. Results Here, we examined the effect of Wnt3a on BDI production in a hypothalamic cell line and hypothalamic tissue. In N39 hypothalamic cells, Wnt3a treatment significantly increased the expression of theIns2 gene, which encodes the insulin isoform predominant in the mouse brain, by activating Wnt/β-catenin signaling. The concentration of insulin was higher in culture medium of Wnt3a-treated cells than in that of untreated cells. Interestingly, neurogenic differentiation 1 (NeuroD1), a target of Wnt/β-catenin signaling and one of transcription factors for insulin, was also induced by Wnt3a treatment in a time- and dose-dependent manner. In addition, the treatment of BIO, a GSK3 inhibitor, also increased the expression ofIns2 andNeuroD1 . Knockdown of NeuroD1 by lentiviral shRNAs reduced the basal expression ofIns2 and suppressed Wnt3a-inducedIns2 expression. To confirm the Wnt3a-induced increase inIns2 expression in vivo, Wnt3a was injected into the hypothalamus of mice. Wnt3a increased the expression ofNeuroD1 andIns2 in the hypothalamus in a manner similar to that observed in vitro. Conclusion Taken together, these results suggest that BDI production is regulated by the Wnt/β-catenin/NeuroD1 pathway in the hypothalamus. Our findings will help to unravel the regulation of BDI production in the hypothalamus.